TELAAH ATAS ADJUDIKASI PUTUSAN KASUS KORUPSI - Widiada Gunakaya (Jurnal Yudisial, 2010)
ABSTRACTAdjudication is the most important stage in the criminal court system, because at this stage, that the defendant's fault must be proven through a court decision. As the final stage of law enforcement in a criminal court proceeding, court decisions normatively should reflect the material truth. And the decision reviewed in this paper, the defendant has been convicted guilty of "criminal acts of corruption collectively" causing the state loss. The judge in this decision, in general, has applied the provisions of Article 197 paragraph (1) of the Criminal Code. Yet pertained to substantive criminal law, the courts have not applied the elements that must meet the sentencing requirements, either in relation to the crime and fault, in the approved manner. Similarly, his legal reasoning has not been through systematically-logically as well. The justice value is not also fully upheld in this decision.Keywords: unlawful nature againts the material law, criminal liability, sentencing requirements, legal reasoning, justice ABSTRAKPutusan hakim merupakan tahap terpenting dalam sistem pengadilan pidana karena pada tahap ini terdakwa harus membuktikan tidak bersalah di muka pengadilan. Sebagai tahap akhir dalam penegakan hukum peradilan pidana, putusan pengadilan secara normatif akan merefleksikan kebenaran materil. Putusan pengadilan ini menjadi kajian dalam tulisan ini dimana terdakwa yang dinyatakan bersalah berdasarkan undang-undang korupsi dengan alasan merugikan negara. Secara umum, hakim memutus mengunakan pasal-pasal 197 paragraf (1) dalam KUHP karena pengadilan tidak mengunakan unsur-unsur yang harus dipenuhi terkait kejahatan maupun kesalahan. Padahal, alasan hukum tidak terlihat secara sistematis dan logik dengan baik. Alhasil, nilai-nilai keadilan tidak terlihat secara jelas dalam putusan tersebut. Kata kunci: sifat melawan hukum materiil, pertanggungjawaban pidana, persyaratan hukuman, alasan hukum, keadilan